Going local: exploring consumer behaviour and motivations for palmyrah based products - Shaliny, S.; Sri thayalan, S. (university of Jaffna, 2014)
In recent years, in Sri Lanka, government pays its focus on promoting palmyrah industry through developing appropriate marketing strategies. Before 1978, this agro-based palmyrah industry was excluded from the Sri Lankan national economic development plans and programmes compared to Coconut and Kithul based industries. Inherent limitations of the palmyrah industry influence the under-development of the sector in relation to socio-economic and cultural nature of the industry. With the establishment of Palmyrah Development Board (1978), improved programmes and actions pertaining to the production and marketing of the palmyrah industry were developed and contributed to develop as a sub-sector of the Sri Lankan agro-based industries. Due to various uncontrollable situations and factors in relation to marketing, the development of palmyrah industry failed to reach to an optimum level. In light of this trend, study on consumer behaviour and motivation pertaining to palmyrah based products (PBP) is becoming crucial. The study explored issues affect consumer motivation and decision. The stimulus-response model of buyer behaviour was adopted in explaining the consumer behaviour of PBP. The research subjects were people who know and are familiar with PBP in traditional marketplaces of North and East provinces, Sri Lanka. Observation, Interviews and Questionnaire were used to collect the qualitative data. Findings of the study showed environmental stimuli were stronger than marketing stimuli. Buyers' characteristics strongly influence the decision process, meanwhile problem recognition, information search and alternative evaluation were found to contribute minimal.
Keywords: Consumer behaviour; Buyer; Palmyrah products; Motivation